Persepsi Siswa Terhadap Pelaksanaan Layanan Klasikal Bimbingan Klasikal - Geandra Ferdiansa; Yeni Karneli; Mudjiran Mudjiran (Ristekdik : Jurnal Bimbingan dan Konseling, 2020)
Students' perceptions of the implementation of classical services in the classroom can be positive or negative, depending on how BK teacher techniques in providing BK services in class. The purpose of this study was to determine how students' perceptions of the implementation of classical guidance services in class and the scope of this study was in SMP 25 Kota Padang in class IX. The method used in this research is descriptive qualitative. Summary of the results of this study are that BK teachers do not need Needs Assessment, material does not meet the needs and the method used by BK teachers is not good. The conclusion of this study is that BK teachers do not carry out Need Assessment to determine material that is in line with the needs of the students and the methods of giving that are not appropriate.